The HPV viral regulatory mechanism of TLRs and the related treatments for HPV-associated cancers - Qi, Shi-Yu; Yang, Miao-Miao; Li, Chong-Yang; Yu, Kun; Deng, Shou-Long (Frontiers in Immunology, 2024)
Infection with human papillomavirus (HPV) typically leads to cervical cancer, skin related cancers and many other tumors. HPV is mainly responsible for evading immune tumor monitoring in HPV related cancers. Toll like receptors (TLRs) are particular pattern recognition molecules. When the body is facing immune danger, it can lead to innate and direct adaptive immunity. TLR plays an important role in initiating antiviral immune responses. HPV can affect the expression level of TLR and interfere with TLR related signalling pathways, resulting in sustained viral infection and even carcinogenesis. This paper introduces the HPV virus and HPV related cancers. We discussed the present comprehension of TLR, its expression and signalling, as well as its role in HPV infection. We also provided a detailed introduction to immunotherapy methods for HPV related diseases based on TLR agonists. This will provide insights into methods that support the therapeutic method of HPV related conditions with TLR agonists.